50 grams test in detecting GDM. - Pacora Portella, Percy (2015)
651 pregnant women at 26 to 36 weeks gestation were tested 1 hour with 50 g oral load of glucose (Test 50 g). They are passing the threshold of greater than or equal 130 mg / dl in plasma were suspicious of Gestational Diabetes (SDG). You're were subsequently tested oral glucose tolerance (OGTT) stop the diagnosis of gestational diabetes mellitus (BG) according to the criteria of the National Diabetes Data Group. The age of pregnant women was 26.3 ± 6.4 years (mean ± SD), range 16-45 years. 310 pregnant women (47.6%) did not have any risk factors for diabetes mellitus. 57 pregnant women (8.7%) were SDG. 32 (4.9%) underwent OGTT, resulting DG 24 patients (3.7%). There was no significant difference in the incidence of BG in people with risk factors and those that had not. The sensitivity of the test was 50 g of 88.9% and specificity of 95.2%. There were 3 DG not detected by the test; so the overall incidence of DG in the study population was 4.1%. The importance of the 50 g test as a screening method in large surveys and their importance in identifying patients by DG greater risk obstetric and perinatal they have on the general population is demonstrated.